Procedures for Returning Movable Cultural Assets that Have Illegally Left the Territory of a Union State - Palade-Ropotan, Mihaela (Acta Universitatis Danubius. Juridica, 2025)
The European Union’s free market allows assets to transit multiple countries without restrictions or prohibitions. At the same time, the cultural assets market has expanded significantly, with a high level of interest, especially visible through the surge of cultural events flooding Europe in post-pandemic times. Nonetheless, the European Union had a well-established legal framework as far back as 1993. The freedoms provided by the Union’s policies regarding the movement of assets have also impacted on this category of assets, which often reflects the history of a people, a country, or evidence of the civilization belonging to a specific geographical area. Whether we are discussing cultural assets owned by the state or cultural assets forming part of private collections, their legal transit and trade have been a constant concern for the Union’s legal bodies and the public authorities of each member state. However, problems arise from the illegal departure of such assets from the territory of a Union state, especially in situations where the assets transit multiple countries and cannot be retrieved. Icons, paintings, artifacts, jewellery, and similar items become objects of interest for individuals seeking illegal profit by removing these assets from Union territories under any circumstances. To address this, the European Union updated legislation in this sector in 2014, to which Romania adhered. Moreover, the aim of this extensive approach is to highlight the constant concern for updating legislation in the country during this period and the awareness of the loss of cultural assets considered treasures.